Pemanfaatan Limbah Kulit Singkong Menjadi Bahan Bakar Bioethanol (Studi Kasus : Usaha Keripik Singkong Pika Kota Pekanbaru): Pemanfaatan Limbah Kulit Singkong Menjadi Bahan Bakar Bioethanol (Studi Kasus : Usaha Keripik Singkong Pika Kota Pekanbaru) - Mugandi, Nabila Meitri (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2023)
UKSP is a business that produces 200-300 kg of cassava chips, resulting in 30-45 kg of cassava peel solid waste. The waste is simply thrown away without further processing, causing environmental damage and producing a foul odour. This research utilises cassava peel waste into bioethanol using fermentation and distillation methods. The calculation of electrical energy and cost savings in this study compares E0, E10 and PLN electricity. Bioethanol potential from 30 kg of cassava peel waste is 5.3280 L/h with a purity of 99.9917%. The potential electrical energy generated using E0 reaches 47.34 kWh, while E10 is 46.89 kWh, and PLN electricity is 1.8 kWh. The fuel cost of E0 was IDR 44,4400 for E10 was IDR 33,000 and PLN electricity was IDR 24,336. The results of the comparison between E0 and E10 are used if electricity tariffs increase in the future so that bioethanol can be utilised as alternative energy for UKSP. Based on the results obtained, E10 is an efficient fuel blend that is feasible to use. In the cost analysis, the total investment in cassava peel utilisation is IDR 3,668,895 and the potential savings per year reaches IDR 5,259,024. The pay-back period is 0.70 years. Keyword: Fuel, Bioethanol, Cassava Waste, Electricity, Superpro